(untitled) (The Peerian Journal, 2025)
The concept of gender has become prevalent with the contemporary feminist movement and an important means of communication that motivates the demand for rights and cultural roles, which emerged from the complex and intertwined relationship between the concept of the biological body and the intellectual transformations that affected its contexts. The body is a vessel that carries the human spirit and a symbol of standards and taboos. It reveals thorny and complex beliefs and concepts that are difficult to penetrate, and reflects the positions of societies that are constantly dialectical towards breaching cautious borders around the body. Due to its importance, this research came under the title “Feminist Movement between Formal Manifestations and Gender Representations in Contemporary Art”. It is concerned with confronting male dominance, highlighting the important role of female artists and their creative works in history, and cooperating with public efforts to support women. The research is concerned with revealing the feminist movement and gender representations in contemporary painting. The descriptive approach is adopted in analyzing research samples and adopting research tools based on what was stated in the theoretical framework.